THE ROLE OF KUNDALINI YOGA IN ALLEVIATING EARLY PREGNANCY DIS-COMFORTS: A PRE-POST TEST EXPERIMENTAL STUDY - Qatrunnada Naqiyyah Khusmitha; Atik Farokah; Herdian Fitria Widyanto Putri (Jurnal Kedokteran Diponegoro)
Background: Recent studies highlight the therapeutic potential of yoga and meditation in pregnancy, particularly for managing anxiety, nausea, and vomiting in pregnancy (NVP). Although some clinical research has established yoga’s benefits, the specific effects of Kundalini Yoga on anxiety and NVP during early pregnancy remain underexplored. Objective: This study examines the effectiveness of Kundalini Yoga in reducing anxiety and NVP levels among pregnant women in their first trimester. Methods: A true experimental study with a pre-posttest randomized controlled design was conducted. A total of 50 pregnant women attending Polindes Mancon, Nganjuk, were randomly assigned to either the treatment group (receiving Kundalini Yoga intervention) or the control group (receiving standard prenatal care). Anxiety and NVP levels were measured using validated questionnaires before and after a four-week intervention period. Results: The treatment group exhibited significant reductions in anxiety (p = 0.039) and NVP levels (p = 0.000) compared to the control group (p < 0.05). Within-group analysis showed that anxiety levels significantly decreased in the treatment group (p = 0.002), while no significant change was observed in the control group (p = 0.102). Additionally, both groups demonstrated improvements in NVP from pre- to post-intervention, though the effect was more pronounced in the treatment group (p = 0.000) compared to the control group (p = 0.013, p < 0.05). Conclusion: These findings suggest that Kundalini Yoga is an effective intervention for reducing anxiety and NVP during early pregnancy, potentially improving both the psychological and physical well-being of expectant mothers. Future research should explore long-term effects and optimal implementation strategies for integrating Kundalini Yoga into prenatal care programs.